PENGARUH LIKUIDITAS, PERTUMBUHAN PENJUALAN, PERPUTARAN MODAL KERJA, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar pada BEI pada Tahun 2014 – 2016) - Suci Rahmawati; M. Agus Salim; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT               The purpose of this research was to study 1) the effect of liquidity to company profitability. 2) The effect of sales growth to company profitability. 3) The effect of working capital turnover to company profitability. 4) The effect of company size to company profitability. 5) The effect of leverage to company profitability. The approach of this research was quantitative. Quantitative approach is an approach by using data in the form of numbers. The population of this research is manufacturing companies that listed on stock exchange in 2014-2016. Sample determination was done by purposive sampling method of judgment sampling, with 30 companies using documentation and literature study in data collection.               Based on the results of the analysis can be concluded: 1) liquidity has a significant effect to company profitability. 2) Sales growth has no significant effect to company profitability. 3) Working capital turnover has no significant effect to company profitability.  4) Company size has no significant effect to company profitability. 5) Leverage has no significant effect to company profitability. Keywords: Liquidity, Sales growth, Working capital turnover, Company size, Leverage and Profitability.